Who owns Appalachia? : landownership and its impact (The University Press of Kentucky, 2015)
Long viewed as a problem in other countries, the ownership of land and resources is becoming an issue of mounting concern in the United States. Nowhere has it surfaced more dramatically than in the southern Appalachians where the exploitation of timber and mineral resources has been recently aggravated by the ravages of strip-mining and flash floods. This landmark study of the mountain region documents for the first time the full scale and extent of the ownership and control of the region's land and resources and shows in a compelling, yet non-polemical fashion the relationship between this co.